The effect of anesthetic agents for oocyte pick-up on in vitro fertilization outcome: A retrospective study in a tertiary center - Esra Nur Tola (Elsevier, 2019)
Objective: General anesthesia is used in most in vitro fertilization (IVF) clinics for oocyte pick-up (OPU), however, there is no consensus on type of anesthetic agent use among clinicians performing OPU. Therefore, we aimed to evaluate the effects of propofol, ketamine, or combination of propofol and ketamine (P + K) for OPU on IVF outcome. Material and methods: Three hundred and thirty three women (n = 333) undergoing IVF treatment were retrospectively included and were evaluated in three groups depending on whether they received propofol (n = 217), or ketamine (n = 60), or P + K (n = 56) for anesthesia during OPU. Results: Baseline characteristics and duration of anesthesia of each group were comparable except lower motile sperm percentage in the ketamine group compared to the propofol group (p = 0.002). Fertilization rate (FR) was decreased with ketamine compared to propofol (p = 0.013) and P + K (p = 0.008). After adjustment for sperm motility, this negative effect of ketamine on FR persisted. Implantation, clinical pregnancy, take-home baby rates, and oocyte retrieval parameters (number of total retrieved oocyte, metaphase II oocytes, embryo and methaphase II rate, and embryo quality) did not differ between the groups. Extended anesthesia duration (>30 min) was associated with low implantation (p = 0.04) and clinical pregnancy rates (p = 0.02). Conclusion: Ketamine use during OPU can affect FR compared to propofol and P + K. Long durations of anesthesia also seem to decrease implantation and clinical pregnancy rates. Keywords: IVF outcome, Anesthesia, Propofol, Ketamine